PENGEMBANGAN BIOSENSOR ELEKTROKIMIA BERBASIS ENZIM ASETILKOLINESTERASE UNTUK ANALISIS RESIDU PESTISIDA PADA PRODUK PERTANIAN - Mashuni, Mashuni (Jurnal Agroteknos, 2012)
Pesticide is one of dangerous chemical compounds in environment. Its existence has spread so it can cause negative effect for human. Pesticide compound is toxic in for nervous system so that a quick detection system is needed to protect human’s health and as a control for agricultural product. Therefore, we conducted a research of electrochemical biosensors development  based  on  enzyme  acetylcholinesterase  in  electrode  to  analyze  pesticide residue  so  that  a  more  superior  and  reliable  biosensors  can  be  obtained  for  pesticide residue analysis in foodstuff samples, especially for agricultural product. Residue analysis of carbamate and organophosphate in foodstuff sample requires a sensitive, selective, cheap- and-easy-operated, and quick-analyzed tools. A new research has been designed in making of  biosensors electrode by  using immobilization method of  enzyme  acetylcholinesterase (AChE) with the supporting materials of Acetate Selulose (AS) and Glutaraldehid (GA) in biosensor electrode connected with electrochemical transducer. Designed biosensors were characterized, including Nernst factor, the detection limit, response time, and period of use. Next,  biosensors  were  tested  in  sample  of  vegetables and  fruits.  Expected  result  was  a biosensor prototype with better work than pesticide determination with instrument of Gas Chromatography (GC) and High Pressure Liquid Chromatography (HPLC). Biosensor development offers low cost, accurate, quick analysis time, and sensitive to detect pesticide residue. Keywords: : Pesticide, Biosensor, Electrochemical, Enzim, Sensitive